DEVELOPMENT OF THE COLLABORATIVE AGRIBUSINESS NETWORK MANAGEMENT MODEL AMONG FARMERS - Chintapitaksakul, Parpitchaya; Khrutmuang Sanserm, Sineenuch; Yooprasert, Benchamas; Teerasukittima , Chaichana (Journal of MCU Nakhondhat, 2026)
The objectives of this research were to study and analyze 1) The network context, 2) The management and key success factors of the network, and 3) Develop model in a collaborative agribusiness network management model among farmers. This study employed a mixed-method research approach. The population consisted of 249 members of the Thai Mango Growers Association network in the LINE group as of January 1, 2024. The sample size of 154 respondents was determined using Yamane’s formula with a sampling error of 0.05 through simple random sampling. Data were collected through in-depth interviews with key informants and interviews with the sample group. The model was developed and evaluated by a total of 30 experts and relevant farmers. Qualitative data were analyzed using content analysis and synthesis, while quantitative data were analyzed using descriptive statistics and exploratory factor analysis. The results of research revealed that 1) The Thai Mango Growers Association adopts a network-based strategy in which farmers voluntarily collaborate in thinking and action, with emphasis on sharing, knowledge exchange, and mutual sacrifice to achieve common goals. 2) The management and key success factors of the network consisted of 12 variables derived from exploratory factor analysis by dimension, with three factors extracted in each dimension as follows: 1) Planning: sustainable production organization, learning organization, and fair business practices 2) Organizing: efficient management system, self-reliance system, and knowledge development system 3) Leading: innovation-driven market system, collaborative working, and knowledge transfer and exchange system and 4) Controlling: mango quality development system, market control system, and supportive organizational culture. And 3) The development of the network management model comprised network context, network management, and key success factors of the network. The overall evaluation of the model in terms of appropriateness, feasibility, and usefulness was at a high level.